The Role of Moral Critical Thinking in Addressing Contemporary Challenges in Da'wah from a Spiritual Counseling Perspective - Alawiyah, Tuti (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2025)
This study aims to explore in depth the role of moral critical thinking in facing contemporary challenges in da'wah, particularly in the context of spiritual counselling. Using a qualitative approach, this study examined the subjective experiences of da'wah practitioners, spiritual counsellors and religious leaders through semi-structured interviews, focus group discussions and document analysis. Through thematic analysis, the study sought to identify major emergent themes related to the application of moral critical thinking in da'wah practice. The primary goal of this study is to emphasise the importance of moral critical thinking in ensuring that da'wah remains an effective tool for social transformation in the modern era, particularly in the face of challenges such as globalisation, pluralism, and rapid technological development. The findings highlight the significance of moral critical thinking in tackling modern issues in da'wah from a spiritual counselling approach. Through in-depth analysis of data collected from interviews, focus group discussions, and document analysis, several key themes emerged, highlighting the need for da'wah practitioners to develop critical thinking skills in navigating the complexities of the digital age, addressing social injustices, and fostering peace and resilience. By integrating moral critical thinking with spiritual counselling, da'wah practitioners can effectively address contemporary challenges, promote ethical engagement, and make meaningful contributions to the spiritual and social well-being of individuals and communities.